Remarks at the World Health Organization Media Briefing on COVID-19 and Vaccine Equity - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass stated that the immediate priority is for countries that have sufficient supply to quickly release doses to countries that have vaccination deployment programs. He said that by the end of June, the World Bank will have approved vaccination operations in over 50 countries. It is vital to speed up the supply chain. The World Bank is providing transparent access to very detailed information about projects through an online portal available at https://www.worldbank.org/vaccines. He urged other development partners to publish detailed information about their vaccine financing and deployment programs and their delivery schedules. The World Bank is also working to expand supply and will be making announcements of investments by IFC, the World Bank Group’s private sector development arm.